EXAMINING THE IMPACT OF HABIT, WORKLOAD, AND WORK ENVIRONMENT TO WORK STRESS ON MILLENNIAL GENERATIONS - Nico Hervian Aldino; Rosaly Franksiska (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The phenomenon that has occurred in recent years is that millennials feel more stressed than other generations who are older at work. Developing a bad habit due to many activities driven by instant life style may have add to this problem. This study examines the effect of habits, workload, and work environment on work stress on millennial generation employees. The research method used in this research is quantitative research using questionnaire with 140 respondents. Using multiple regression analysis, this study shows the results that habits have a positive influence on work stress on millennial generation employees, the workload does not influence work stress on millennial generation employees, and the work environment negatively influence work stress on millennial generation employees. Keywords: Habit, Workload, Work Environment, Work Stress, Millennials